Clinical features and outcomes of spinal cord infarction following vertebral artery dissection: a systematic review of the literature. (1st September 2013) - Hsu, Chia-Yu; Cheng, Chun-Yu; Lee, Jiann-Der; Lee, Meng; Huang, Ying-Chih; Wu, Chih-Ying; Hsu, Huan-Lin; Lin, Ya-Hui; Huang, Yen-Chu; Weng, Hsu-Huei; Huang, Kuo-Lun
<x xml:space="preserve">Abstract</x> Objective: Spinal cord infarction (SCI) is a rare complication of vertebral artery dissection (VAD). Its clinical features and outcomes have not yet been well documented. Methods: In addition to reporting a case with bilateral SCI caused by left VAD, we performed a systematic review of the literature conducted through a PubMed search. Results: A total of 17 cases were reviewed (nine men and eight women). The average age was 40·5±14·6 years. In addition to neck pain or headache (88%), patients with VAD-associated SCI often presented with a sensory level (76%) or Brown-Séquard syndrome (53%). The most common regions of dissection were at the V1 or proximal V2 segments, and the infarcted area of SCI was mainly located at C2-C5 levels. Regarding the vascular territory, posterior spinal artery infarction was noted in 29% of patients, spinal sulcal artery infarction in 42%, and anterior spinal artery (ASA) watershed infarction in 29%. Eleven patients (65%) had a good outcome and six patients (35%) had a poor outcome (including one mortality; 6%). Smoking, age above 50 years, and ASA watershed infarction were associated with a poor outcome, while spinal sulcal artery infarction was associated with a good outcome. Conclusion: Neck pain or headache is an important warning symptom of VAD, and the presence of a concomitant sensory level or Brown-Séquard syndrome is helpful for the early diagnosis of SCI caused by VAD. One-third of patients had a poor outcome, and smoking, old age, and ASA watershed infarction represented important risk factors.